Impact of socioeconomic factors on paediatric cochlear implant outcomes. (November 2017) - Sharma, Shalabh; Bhatia, Khyati; Singh, Satinder; Lahiri, Asish Kumar; Aggarwal, Asha
Abstract: Objectives: The study was aimed at evaluating the impact of certain socioeconomic factors such as family income, level of parents' education, distance between the child's home and auditory verbal therapy clinic, and age of the child at implantation on postoperative cochlear implant outcomes. Methods: Children suffering from congenital bilateral profound sensorineural hearing loss and a chronologic age of 4 years or younger at the time of implantation were included in the study. Children who were able to complete a prescribed period of a 1-year follow-up were included in the study. These children underwent cochlear implantation surgery, and their postoperative outcomes were measured and documented using categories of auditory perception (CAP), meaningful auditory integration (MAIS), and speech intelligibility rating (SIR) scores. Children were divided into three groups based on the level of parental education, family income, and distance of their home from the rehabilitation– auditory verbal therapy clinic. Results: A total of 180 children were studied. The age at implantation had a significant impact on the postoperative outcomes, with an inverse correlation. The younger the child's age at the time of implantation, the better were the postoperative outcomes. However, there were no significant differences among the CAP, MAIS, and SIR scores and each of the three subgroups. Children from families with an annual income of less than 7, 500, between 7, 500 and 15, 000, and more than 15, 000 performed equally well, except for significantly higher SIR scores in children with family incomes more than 15, 000. Children with of parents who had attended high school or possessed a bachelor's or Master's master's degree had similar scores, with no significant difference. Also, distance from the auditory verbal therapy clinic failed to have any significantimpact on a child's performance. Discussion: These results have been variable, similar to those of previously published studies. A few of the earlier studies concurred with our results, but most of the studies had suggested that children in families of higher socioeconomic status had have better speech and language acquisition. Conclusions: Cochlear implantation significantly improves auditory perception and speech intelligibility of children suffering from profound sensorineural hearing loss. Younger The younger the age at implantation, the better are the results. Hence, early implantation should be promoted and encouraged. Our study suggests that children who followed the designated program of postoperative mapping and auditory verbal therapy for a minimum period of 1 year seemed to do equally well in terms of hearing perception and speech intelligibility, irrespective of the socioeconomic status of the family. Further studies are essential to assess the impact of these factors on long-term speech acquisition andlanguage development.